Gambaran Pengetahuan Tentang Mencuci Tangan pada Anak Sekolah Dasar: Kelas 4 Dan 5 di SD Inpres 126 Parappunganta I Kecamatan Polut Kabupaten Takalar - Nur Atika; Muhamad Isnaini; Asriani Bahar (Fatiakara Care: Jurnal Ilmiah Keperawatan, 2025)
Learning to wash hands properly to children can be taught as early as possible because it improves children's abilities and resilience and makes children able to look after or care for themselves. Washing hands is an action to prevent and control disease which is part of the clean and healthy living behavior (PHBS) program in schools. The method in this research uses quantitative research with a descriptive design. The research results showed that the level of knowledge about how to wash hands properly and correctly is an area that requires more attention in public health programs, especially because the majority of respondents of both genders have inadequate knowledge. Higher parental education was associated with children's better knowledge about hand washing. In contrast, lower parental education tends to correlate with children's lack of knowledge about these practices. Health education efforts should be more focused on families with lower parental education to improve children's understanding and basic health practices